Combining a robust thermophilic methanogen and packing material with high liquid hold-up to optimize biological methanation in trickle-bed reactors. (February 2022) - Kaul, Anja; Böllmann, Andrea; Thema, Martin; Kalb, Larissa; Stöckl, Richard; Huber, Harald; Sterner, Michael; Bellack, Annett
Graphical abstract: Highlights: The liquid flow has a main effect on the hold-up while the gas flow is negligible. Methanothermobacter strains better for methanation than Methanothermococcus strains. Pure cultures and packings have to be well-matched to maximize methane quality. Mtb. thermoautotrophicus IM5 + DuraTop® ideal for ORBIT-trickle-bed system. Abstract: The hydrogen gas-to-liquid mass transfer is the limiting factor in biological methanation. In trickle-bed reactors, mass transfer can be increased by high flow velocities in the liquid phase, by adding a packing material with high liquid hold-up or by using methanogenic archaea with a high methane productivity. This study developed a polyphasic approach to address all methods at once. Various methanogenic strains and packings were investigated from a microbial and hydrodynamic perspective. Analyzing the ability to produce high-quality methane and to form biofilms, pure cultures of Methanothermobacter performed better than those of the genus Methanothermococcus . Liquid and static hold-up of a packing material and its capability to facilitate attachment was not attributable to a single property. Consequently, it is recommended to carefully match organism and packing for optimized performance of trickle-bed reactors. The ideal combination for the ORBIT- system was identified as Methanothermobacter thermoautotrophicus IM5 and DuraTop®.